Factors affecting milk market outlet choices in Wolaita zone, Ethiopia - Kuma, B.; Baker, Derek; Getnet, Kindie; Kassa, B. (Academic Journals, 2013)
The study was undertaken with the objective of assessing factors affecting milk market outlet choices in Wolaita zone, Ethiopia. Using farm household survey data from 394 households and Multinomial Logit Model, milk market outlet choices were analyzed. Multinomial Logit model results indicate that compared to accessing individual consumer milk market outlet, the likelihood of accessing cooperative milk market outlet was lower among households who owned large number of cows, those who considered price offered by cooperative lower than other market outlets and those who wanted payment other than cash mode. The likelihood of accessing cooperative milk market outlet was higher for households who were cooperative member, who owned large landholding size, who had been in dairy farming for many years and who received better dairy extension services. Compared to accessing individual consumer milk market outlet, the likelihood of accessing hotel/restaurant milk market outlet was lower among households who were at far away from urban center and higher among households who accessed better dairy extension services and who owned large number of dairy cows. As one of the key factors to boost milk market outlet choices, dairy extension services should be strengthened through redesigning or reforming implementation strategies or improving/strengthening existing policy. It should be strengthened to enable farmers produce surplus milk for markets and should devise means to reduce local milking cow numbers by replacing them with crossbred cows. Moreover, governments should strengthen milk processing cooperatives and improve infrastructure facilities.